Penerapan Model Numbered Head Together (NHT) Terhadap Hasil Belajar Kognitif Siswa Di SMA - Sukarman Hadi Jaya Putra (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to analyze the effect of the numbered head together (NHT) model on critical thinking skills and cognitive learning outcomes. This research is action research conducted in the classroom, or classroom action research (Classroom Action Research). Classroom action research is research conducted by teachers in the classroom by (1) planning, (2) implementing (3) observing and (4) reflecting on collaborative and participatory actions with the aim of improving their performance as teachers, so that student learning outcomes can increase. The results showed that the application of the numbered head together type of cooperative learning model can affect critical thinking skills and cognitive learning outcomes for class XI SMAN 1 Maumere,